Elements of chemical process engineering - Jones, D. S. J (John Wiley & Sons, 1996)
Drawing on his own extensive experience, Jones provides rules of thumb essential for the new engineer in industry. Covering responsibilities such as project management, installation of new facilities and implementation of contracts, this book offers a wealth of experience and knowledge, helping newer process engineers to find a foothold in their chosen industry.